The Effectiveness of Synergistic Enzymatic Reaction with Limited Mediator - Dapkūnas, Ž. (Nonlinear Analysis: Modelling and Control, 2007)
Kinetics of biocatalytical synergistic reactions has been analyzed with special emphasis on stability and reactivity of mediators. The application to the model of kinetic constants taken from the experiments showed that the quasi steady state (QSS) for reduced and oxidized enzyme was achieved in 0.001 s. However, the QSS for the mediator was not established during measurable time. For this reason the kinetics of biocatalytical synergistic reactions was modeled by solving the ordinary differential equations using software package KinFitSim©. The calculations showed the increase of an apparent life-time of the mediator in the synergistic reaction. The apparent life-time was most affected by reactivity of mediator. The change of the mediator reactivity from 1 M−1s−1 to 105 M−1s−1 increased the apparent life-time from 19 s to 1538 s. This mediator reactivity can be achieved even for strongly endothermic reaction when difference of redox potential of substrate and mediator is 0.35 V. The increase of mediator life-time increased product yield.